Relational analysis of farmers’ profile with their perception on capacity needs under NICRA villages - Manju Prem Shiva Reddy; Jayalekshmi Gopalakrishnan Nair; Mohanraj Murugan; Soumya Ranjan Behera; Riza Mathew (Annals of Agricultural Research, 2026)
This study investigated the link between farmers’ personal and farming characteristics and their perception on capacity needs under the NICRA programme in Kerala and Karnataka. Data were collected from 160 farmers across four villages using interviews and analysed with descriptive statistics, correlation, and regression. Results showed that most farmers were smallholders, male, and had limited education, with marginal landholdings and mixed or diversified farming systems. Farmers’ perception of capacity needs was mainly influenced by extension contact, participation in training, education, and association with KVK activities. Extension contact was the strongest factor, especially in Karnataka, while education and KVK linkages were more important in Kerala. The findings suggest that frequent extension interaction, practical training, and suitable educational support are key for building farmer capacity in climate-resilient agriculture.